Rejection of Criminal Sanctions on Perpetrators of Domestic Rape (Gender Activist Perspective) - Rahmawati, Rita; Umam, Misbahul Fuadil (Asian Journal of Law and Humanity, 2024)
This study aims to analyze the views of gender activists on the MUI Fatwa Number 02/MUNAS-IX/MUI/2015 on the rejection of criminal sanctions for perpetrators of domestic rape and to find out the legal arguments of the informants related to this fatwa . Domestic sexual violence is an important issue and is often ignored in society. This study uses a field research method with an interactive qualitative approach using primary data sources obtained by interview techniques with informants, namely activists of the UIN KH Abdurrahman Wahid Pekalongan gerder, and secondary data in the form of literature from research books obtained by documentation techniques. The data was analyzed using interactive model qualitative data analysis techniques.The results of the study concluded that gender activists' views vary regarding the fatwa. Several activists have different views on this fatwa. However, all of them reject the fatwa on sexual coercion in the household as not sexual violence because it is considered not to support protection for victims and strengthens patriarchal norms. Arguments from gender activists refer to the Domestic Violence Law which categorizes domestic rape as sexual violence . This study suggests that the fatwa be reviewed and accompanied by case studies to increase public understanding and acceptance and provide appropriate legal solutions for perpetrators of domestic rape.